Establishment of an interdisciplinary vascular anomalies program in Tanzania, East Africa - Puhr-Westerheide, Daniel; Masthoff, Max; Shah, Jay; Krechel, Alina; Shemwetta, Mwivano; Naif, Azza A.; Ukweh, Ofonime N.; Abdul, Ziad; Sarkar, Abizer; Baraka, Balowa Musa; Malecela, Furaha; Lekasio, Praygod Justin; et al. (Frontiers in Medicine, 2023)
Purpose The aim of this project is the sustainable implementation of a vascular anomalies (VA) program in Tanzania. Material and Methods In 2021 the first interdisciplinary VA program was initiated at Muhimbili National Hospital (MNH), Dar Es Salaam, Tanzania in a stepwise approach. During the planning phase the clinical need for minimally-invasive therapies of VAs and the preexisting structures were assessed by the local Interventional Radiology (IR) team at MNH. During the initiation phase, an IR team from two German VA centers joined the interdisciplinary team at MNH for clinical workup, image-guided procedures and follow-up. VA patients were recruited from existing patient records or seen at clinics as de-novo presentations following nationwide advertisement. In the post-processing phase joined online conferences for follow-up and support in management of new patients were established. Further follow-up was supported by attending providers from other established VA centers, travelling to bolster the primary operators of MNH. Results The first interdisciplinary VA program was successfully launched in Tanzania. Minimally-invasive treatments were successfully trained, by performing ultrasound-guided sclerotherapy with polidocanol and bleomycin in twelve patients with slow-flow malformations, one endovascular embolization of a high-flow malformation, and medical treatment of an aggressive infantile hemangioma. Regular online follow-up presentations have been initiated. Follow-up evaluation and required treatment was sustained when appropriate. Conclusion The presented “hands-on” training set the ground for the first interdisciplinary VA program in Tanzania. This framework is expected to establish comprehensive and sustainable care of patients with VAs in East Africa and can serve as a blueprint for other sites.